(untitled) (Revista Brasileira de Plantas Medicinais, 2000)
The objective of the present work was to study the pollination in basil (Ocimum basilicum L.), in order to verify its attractiveness for honey bees (Apis mellifera), the most frequent insects, as well as its behaviors and effects on the production of seeds. The basil flower lasted, on average, 30 hours, from the bud phase until the flower withered. The number of flowers opened by inflorescence was, on average, 5,65±1.42 flowers, and the inflorescence presented a mean of 160±11,73 flowers-buds. The basil was visited mainly by afncanized honey bee (98,0%), followed by the native bee Augochloropsis electra-Halictidae (2.0%) and sporadic visits of Diptera and Lepidoptera. All insects collected only nectar in the culture and delayed of 1 to 3 seconds in each flower. The frequency of the honey bee increased in elapsing of the day to 14:00. decreasing soon after accompanying the curve of the temperature sets registered in the days of the experiment and also the increase in nectar concentration of the flowers. The basil can be considered an important nectar source to africanized honey bees.